What happened to goodbye - Dessen, Sarah (New York Viking, 2011)
Following her parents' bitter divorce as she and her father move from town to town, seventeen-year-old Mclean reinvents herself at each school she attends until she is no longer sure she knows who she is or where she belongs
1
Keywords: Divorce -- Fiction; High schools -- Fiction; Identity -- Fiction; Schools -- Fiction